COMPOSITION ANALYSIS OF RESULTS OF FISHING GARNING NETWORKS BASED ON DIFFERENCES OF NETWORK SIZES AND OPERATING TIME IN MESKOM VILLAGE, BENGKALIS DISTRICT, BENGKALIS DISTRICT - Pranoto, Edwin; Bustari, Bustari; Usman, Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTCatching is an effort made by humans to be able to get the organisms that are in the waters, to get these organisms a fishing gear is needed. The purpose of this study was to determine the composition of catches of species and number of fish using drift gill nets with mesh sizes of 3 and 6 inches at day andnight in the village of Meskom. This research was conducted on 31 August to 13 September 2018 inMeskom Village. The method used is the survey method, in which the researcher descends directly into the field and participates in the process of operating the Gill Net fishing gear. The results obtained were 22 species of fish weighing 258.63 kg from 565 fish.The results of the mesh size of 3 inches during the study obtained 523 tails with a total weight of 224.97 kg, during the day 259 tails (104.18 kg), while at night 264 tails (120.79 kg). The results of the 6-inch mesh size during the study obtained 42 tails with a total weight of 33.66 kg. Day 5 tails (2.29 kg), and nights 37 tails (31.37 kg).Based on the 3-inch mesh size t-test day and night, it was found that the t-count 0.85305 was smaller than the 1.7341 table so that the null hypothesis (H0) was accepted, there was no difference in the catch between day and night on the 3-inch mesh size in the Meskom village Bengkalis Bengkalis Regency.While the mesh size is 6 inches, the t-test obtained is 2.7044, greater than the 1.9432 table, so the null hypothesis (H0) is rejected because there are differences in catches between day and night on the 6 inch mesh size in the Meskom village,Bengkalis District Bengkalis..Key word :Gill Net, Difference in Mesh Size and Time, Capture Results.